Exploration of Sulfur Assimilation of Aspergillus fumigatus Reveals Biosynthesis of Sulfur-Containing Amino Acids as a Virulence Determinant - Amich, Jorge; Duemig, Michaela; O'Keeffe, Grainne; Binder, Jasmin; Doyle, Sean; Beilhack, Andreas; Krappmann, Sven (Infection and Immunity, 2016)
Fungal infections are of major relevance due to the increased numbers of immunocompromised patients, frequently delayed diagnosis, and limited therapeutics. To date, the growth and nutritional requirements of fungi during infection, which are relevant for invasion of the host, are poorly understood. This is particularly true for invasive pulmonary aspergillosis, as so far, sources of (macro)elements that are exploited during infection have been identified to only a limited extent. Here, we have investigated sulfur (S) utilization by the human-pathogenic mold Aspergillus fumigatus during invasive growth. Our data reveal that inorganic S compounds or taurine is unlikely to serve as an S source during invasive pulmonary aspergillosis since a sulfate transporter mutant strain and a sulfite reductase mutant strain are fully virulent. In contrast, the S-containing amino acid cysteine is limiting for fungal growth, as proven by the reduced virulence of a cysteine auxotroph. Moreover, phenotypic characterization of this strain further revealed the robustness of the subordinate glutathione redox system. Interestingly, we demonstrate that methionine synthase is essential for A. fumigatus virulence, defining the biosynthetic route of this proteinogenic amino acid as a potential antifungal target. In conclusion, we provide novel insights into the nutritional requirements ofA. fumigatus during pathogenesis, a prerequisite to understanding and fighting infection.
EVALuna2:7707